+0  
 
 #1
avatar+627 
+2

We can start by replacing b with (a-1).

 

\begin{align*} (a-1)^2\cdot a^0&=7\cdot a^1+1\cdot a^0
\\\Rightarrow\qquad a^2-2a+1&=7a+1
\\\Rightarrow\qquad a^2-9a&=0
\\\Rightarrow\qquad a(a-9)&=0
\end{align*}

 

So we can have 0 or 9.

 

But there is no base 0, so must be base 9. 

supermanaccz  Mar 21, 2018
 #2
avatar+195 
0

thanks

Rollingblade  Mar 22, 2018
 #3
avatar+627 
0

Oh yay! My LaTeX finally worked for once. 

supermanaccz  Mar 30, 2018

44 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.